The French Navy and the Seven Years' War - Dull, Jonathan R., 1942- (France overseas., 2005)
The Seven Years' War was the world's first global conflict, spanning five continents and the critical sea lanes that connected them. This book is the fullest account ever written of the French navy's role in the hostilities. It is also the most complete survey of both phases of the war: the French and Indian War in North America (1754-60) and the Seven Years' War in Europe (1756-63), which are almost always treated independently. By considering both phases of the war from every angle, award-winning historian Jonathan R. Dull shows not only that the two conflicts are so interconnected that neither can be fully understood in isolation but also that traditional interpretations of the war are largely inaccurate. His work also reveals how the French navy, supposedly utterly crushed, could have figured so prominently in the War of American Independence only fifteen years later. A comprehensive work integrating diplomatic, naval, military, and political history, The French Navy and the Seven Years' War thoroughly explores the French perspective on the Seven Years' War. It also studies British diplomacy and war strategy as well as the roles played by the American colonies, Spain, Austria, Prussia, Russia, Sweden, and Portugal. As this history unfolds, it becomes clear that French policy was more consistent, logical, and successful than has previously been acknowledged, and that King Louis XV's conduct of the war profoundly affected the outcome of America's subsequent Revolutionary War.